Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.53402/ijesss.v1i3.34
|View full text |Cite
|
Sign up to set email alerts
|

University students’ perception of online learning: A case study of Virtual Class learning management system in the University of Lampung

Abstract: The use of online media to facilitate distant learning during the pandemic has become one of the solutions that can be implemented to support the government's policy of reducing crowds in public spaces. In this case, students at the University of Lampung's Faculty of Teacher Training and Education benefit from an online management system called Virtual Class Unila. This platform is intended for students to use to access resources, download learning modules, and participate in classroom discussions. The Virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…The third questionnaire showed that LMS is a better e-learning tool for online learning platforms. That result is similar to the previous studies that mentioned that LMS (Learning Management System) is one of the alternatives for an online class (Octaberlina & Muslimin, 2020;Riyantika et al, 2021). LMS tool is effectively used, benefits, and motivates students in online learning (Tseng, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The third questionnaire showed that LMS is a better e-learning tool for online learning platforms. That result is similar to the previous studies that mentioned that LMS (Learning Management System) is one of the alternatives for an online class (Octaberlina & Muslimin, 2020;Riyantika et al, 2021). LMS tool is effectively used, benefits, and motivates students in online learning (Tseng, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…There were several previous studies observed about LMS (Learning Management System) as e-learning tool. Octaberlina & Muslimin (2020) and Riyantika et al, (2021) observed that LMS (Learning Management System) is one of the alternatives for an online class. Tseng (2020) observed that LMS tool is effectively used, benefits, and motivates students in online learning.…”
Section: Introductionmentioning
confidence: 99%
“…Idris, & Masrom, 2022). Saat ini masih terdapat beberapa mahasiswa yang kurang familiar dengan dengan LMS Moodle, hal ini sependapat dengan hasil penelitian Fajar (Riyantika, Nisa, & Kadaryanto, 2021), karena hanya sedikit dosen yang memanfaatkannya. Berdasarkan hasil uji t (paired sample test) bahwa kesimpulan yang dapat ditarik dalam penelitian ini ialah terdapat pengaruh implementasi flipped classroom berbasis moodle pada matakuliah microteaching terhadap kompetensi pedagogik calon Guru.…”
Section: Discussionunclassified
“…United Arab Emirates students valued virtual classes as a medium that interestingly provided scientific material and increased the possibility of contact between students and between students and teacher during the social isolation due to the pandemic [14]. In another study with university students in Indonesia during the pandemic, it was found that most students considered virtual classes to be very helpful [15]. Likewise, Maatuk et al [16] reported that students and teachers of information technology at a university in Libya valued, in a more significant proportion, the advantages of e-learning in virtual classes due to the pandemic.…”
Section: Introductionmentioning
confidence: 99%